Efeitos de duas modalidades de ventilação não invasiva, imediatamente após a extubação, sobre o padrão respiratório de recém-nascidos pré-termo de muito baixo peso - Bruna da Silva Pinto Pinheiro Vieira (2018)
The effects of noninvasive ventilation on the respiratory function of preterm infants have not been fully elucidated. Currently, two modalities of noninvasive ventilation are commonly used in Brazilian Neonatal Intensive Care Units, continuous positive airway pressure (CPAP) and nasal intermittent positive pressure ventilation (NIPPV) nonsynchronized. In this study, it was hypothesized that nonsynchronized NIPPV, by offering two levels of positive airway pressure, could promote greater ventilation (increase of tidal volume and minute ventilation) when compared to CPAP. The main objective of this study was to evaluate the effects of two modalities of noninvasive (CPAP and NIPPV nonsynchronized), immediately after extubation, on the variables of the breathing pattern of very low birth weight preterm infants. In addition, the pain and degree of respiratory discomfort were evaluated. 11 preterm infants were studied, with gestational age and birth weight of 28.78 weeks and 1076.58 grams, respectively. Data collection occurred between july 2017 and july 2018. Soon after extubation, the newborns were randomized into the CPAP-NIPPV (sequence 1) or the NIPPV-CPAP (sequence 2) sequences, determined by sealed envelope. A pressure of 6 cmH2O was used in the CPAP and the following parameters in NIPPV mode: inspiratory pressure= 15 cmH2O, PEEP= 6 cmH2O, breathing frequency= 24 times, inspiratory time = 0.40. Each preterm infant was studied for a period of 60 minutes in each of the modes. Respiratory inductance plethysmography was used to evaluate variables of breathing pattern (tidal volume, respiratory rate, minute ventilation, mean inspiratory flow, inspiratory duty cycle) and thoracoabdominal motion (percentage of contribution of rib cage to tidal volume, percentage of contribution of abdomen to tidal volume, phase relation in inspiration, phase relation in expiration, phase relation in total breath, phase angle and labored breathing index). The neonatal infant pain scale (NIPS) and the Silverman-Andersen index were used to assess pain and respiratory distress in both modalities, respectively. All data collection was performed by a trained physiotherapist. For inferential analysis, ANOVA was used for repeated measurements or Friedman, followed by post hoc Bonferroni and Wilcoxon, respectively; whether applicable. The distribution of the variables data was evaluated by the Shapiro-Wilk test. It was considered significant p<0.05. A total of 7,564 respiratory cycles were analyzed. Regarding the results of breathing pattern and thoracoabdominal movement in the two modalities of noninvasive ventilation, no significant difference was observed in any of the comparisons made for any of the variables analyzed (p>0.05). Regarding the degree of respiratory discomfort, no significant differences were observed in any of the comparisons (p>0.05). The score observed on the neonatal infant pain scale, 20 minutes after an extubation, was significantly higher in the NIPPV mode when compared to CPAP (1.36 ± 1.80 versus 0.64 ± 1.12; p = 0.039). In conclusion, the results showed that there was no significant difference between the two modalities of noninvasive ventilation for variables of pattern, thoracoabdominal movement and degree of respiratory discomfort. The NIPS score pain in the initial part after extubation was higher in NIPPV when compared to CPAP. However, both values are under the level considered as pain.